Alasan Lima Negara ASEAN Melakukan Dedolarisasi Terhadap Dolar US - Davina Aurelia Rachma; Renika Ayu Puspita Sari; Zahra Nisrina Naura Sunardi; Rinandita Wikansari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
The high level of dominance of the US dollar as a global transaction tool has many significant negative impacts on its adherent countries, including the 5 ASEAN countries which include Philippines, Indonesia, Malaysia, Singapore and Thailand. This research aims to make observations regarding the reasons that strengthen the dedollarization phenomenon as well as things that might arise during this process. This research uses a literature study method obtained through various trusted sources. The findings in this research explain that the decision to use a currency to be used as a global transaction tool is initially determined by the strength of the currency itself (in this case the US Dollar), as the level of dominance increases, resulting in the desire for various parties to prioritize its use. Local Currency Settlement (local currency). Those who decide to actualize dedollarization must adopt the various processes that previous countries have gone through that are considered successful. However, this certainly contains many stones, especially since dedollarization efforts have only had limited success.